Mixed Red-Complex Bacterial Infection in Periodontitis - N. Suzuki; M. Yoneda; T. Hirofuji (International Journal of Dentistry)
The red complex, which includes Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia (formerly Bacteroides forsythus), are recognized as the most important pathogens in adult periodontal disease. These bacteria are usually found together in periodontal pockets, suggesting that they may cause destruction of the periodontal tissue in a cooperative manner. This article discusses the interspecies pathogenic interactions within the red complex.